What Do News Editorials Point to in the Framing of Nigerian National Security? Does Media Content Project Public Lens or Elites Power Hierarchies? - Muhammad Hamisu Sani (International Journal of Media and Communication Research, 2024)
Growing cases of the role of media in national security tend to suggest that news is reflective of on the spot assessment. Yet, a corpus of literature shows that media influence is highly dominated by elites’ power, where media framing projects more of these power and influence. This paper therefore expounds on the extent to which news media editorials are reflective of public concerns or portray more of elites’ power. Succinctly, the aim is to explore what media editorials point to in the framing of national security issues. In view of the precarity of insecurity and mounting challenges of Nigeria’s national security, it is pertinent to unravel what constantly preoccupies media establishments, mostly, their editorial contents. And what trajectory and path do they tilt towards in the broader mediatization of the nation’s national issues occasioned by terrorism, militancy, banditry, kidnapping and other crimes. Overall, the paper provides a clue about how news editorials showcase and often pander to hierarchal power within Nigeria’s national security architecture.